The Ethanol Dip and Vapor Delays Chilling Injury of Cucumber (Cucumis Sativus L. cv. Ceylan), During Storage.: Ethanol Treatments for Decreasing Chilling Injury of Cucumber - Kasim, Rezzan; Kasim, Mehmet Ufuk; Yasar, Kubra; Sahin, Tugce (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
In this study, the effects of ethanol which is applied in different forms as liquid and vapor after harvest on chilling injury, color and overall quality of cucumber (Cucumis sativus L. cv. Ceylan) during storage were examined. For the liquid ethanol treatments, cucumber fruits were immersed in water comprising different concentration of ethanol for 5 minutes. In order to apply ethanol in the form of steam, a pad was firstly impregnated with ethanol at different doses. This pad was placed in a polystyrene foam dishes, and after the cucumber fruit is placed on it, the dishes wrapped with stretch film. The doses for used the both ethanol treatment as: Controldip(CD), Controlvapor (CV), 200 µL/L, 400 µL/L , 800 µL/L and 1600 µL/L. It was concluded that the liquid ethanol treatment at the dose of 1600 µL/L was effectively delayed of chilling injury, softening and decay rate.